PERANCANGAN VIRTUAL YOUTUBER SEBAGAI MEDIA PEMBELAJARAN KOSAKATA BAHASA JEPANG TINGKAT PEMULA - Ponsen, Keygi Nisatazkiyah Floresti; Setiana, Soni Mulyawan (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2023)
Learning media is a tool to support the learning process to run well. In Japanese language learning, there is a problem where students find it difficult to memorize vocabulary which is one of the important points in learning the language. This research aims to describe the process of creating learning media using Virtual Youtuber (Vtuber) which is an online entertainer that appears as a virtual avatar in the form of 2 dimensions or 3 dimensions by utilizing motion capture technology. This learning media uses ADDIE model for development, Live2D and IoLive as software to animate the Vtuber model. The result is Japanese vocabulary learning videos that can be accessed through Youtube channel. This learning media is suitable for beginner level Japanese learners. Keywords: Virtual Youtuber, Live2D, learning media, Japanese vocabulary